Contrast-enhanced ultrasonography findings of LAMNs with peritoneal and splenic metastases: a case report and literature review - Chen, Mei; Zhang, Shengmin; Xu, Youfeng; Jia, Xiupeng; Shi, Yijiu (Frontiers in Oncology, 2023)
Low-grade appendiceal mucinous neoplasms (LAMNs) are rare appendiceal tumors primarily diagnosed by computer tomography(CT) enhancement and magnetic resonance imaging (MRI). Herein, we report the sonographic features, especially for contrast-enhanced ultrasound (CEUS) in a 70-year-old female with an unusual LAMN metastasizing to the peritoneum and spleen. The patient had a right pelvic mass observed 2 days ago. Two-dimensional (2D) ultrasound revealed a mixed cystic-solid mass in the right lower abdomen and spleen parenchyma; CEUS showed heterogeneous enhancement in both areas, suspected to be a mucinous mass. CT enhancement and MRI findings revealed concurring findings. Histopathologically, LAMN lesions were confirmed in the appendix, spleen, and peritoneum for specimens obtained during exploratory laparoscopy. No recurrences have been reported in three years postoperatively. LAMN lesions may metastasize to abdominal organs, and imaging examinations are essential to diagnose. This study presents major ultrasonography and CEUS findings to diagnose LAMNs.